PROPOSAL FOR TECHNOLOGICAL MODIFICATION IN A CUBAN DISTILLERY BASED ON A CONSUMPTION INDEXES STUDY - Orisleidy Carrazana Díaz; Ana Celia de Armas Martínez; Yailet Albernas Carvajal; Irenia Gallardo Aguilar (Revista Centro Azúcar, 2021)
Introduction: There are several distilleries in Cuban central region that are characterized by obtaining high quality alcohol as their main product. Technological schemes installed in each one are different, therefore, production can be carried out more efficiently or not taking into account water and steam consumption. Objective: To analyze the technologies in distilleries A and B that produce extrafine alcohol to propose modifications in the less efficient technology according to the one that performs better. Materials and Methods: Processes in the two analyzed distilleries were studied through material and energy balances, taking into account the operating characteristics of each industry. Results and Discussion: Distillery B has a lower steam and cooling water consumption per hectoliter of produced alcohol, due to energy use in certain process streams, such as alcoholic vapors coming out of the rectifier and hydroselector columns. Conclusions: A redistribution of streams in Distillery A reduces the cooling water and steam consumption rate by 35.3 % and 18.9 % of their current values. In this way, only steam generated by the boiler is needed for distillation and final rectifier columns.